P-048 Fertilization rate and embryonic development after intracytoplasmic sperm injection (ICSI) using a microfluidic sperm selection device without centrifugation. (30th June 2022) - Tsuji, H; Kitasaka, H; Fukunaga, N; Asada, Y
Abstract: Study question: Can the use of a microfluidic sperm selection device without centrifugation simplify the procedure without affecting fertilization rates and embryonic development after ICSI? Summary answer: The microfluidic device can be used to select sperm in a simple procedure without reducing the fertilization or embryo development rate. What is known already: In human ART, it is essential to process the semen and adjust the sperm sample according to the intended purpose, rather than using raw semen. Current sperm preparation methods at most IVF clinics include the density gradient centrifugation method, which utilizes the difference in density between the maturation stages of sperm, followed by washing using centrifugation. However, these methods require a lot of steps and the procedure is complicated. Recently, several non-centrifugal sperm processing devices have become available. One of them is a simple sperm conditioning method using a microfluidic device. Study design, size, duration: This was a prospective study using sibling oocytes including 20 ART patients treated with 24 cycles and where there were 320 zygotes after ICSI. The duration of the study was 8 months (May 2020 to December 2020). Participants/materials, setting, methods: For sperm preparation without centrifugation, a microfluidic device "ZyMōtⓇ Multi 850μL" was used. According to the labelled use, 850μL of semen was required with "ZyMōtⓇ" device (ZyMōt group), and the rest of the semen was processed according to routine laboratory procedure by monolayer density gradient centrifugation and washing by centrifugation (DGC group). Oocytes from the same patient were randomly divided into 2 batches and ICSI was performed using sperm treated with each method. Main results and the role of chance: The 2PN formation rate in the ZyMōt group was 84.5% (142/168), which was not significantly different from 82.9% (126/152) in the DGC group. There was also no significant difference in 1PN formation rate (3.0% vs. 3.3%), multi PN formation rate (3.6% vs. 3.3%) and the non-fertilization rate (8.3% vs. 10.5%). The good quality embryo rate at Day 3 was 25.0% (31/124) in the ZyMōt group and 24.5% (27/110) in the DGC group, with no significant difference. The Day 5 blastocyst rate was 37.9% (47/124) in the ZyMōt group and 36.7% (40/109) in the DGC group, and the cumulative blastocyst rates by Day 7 were 54.0% (67/124) and 57.8% (63/109), respectively, with no significant difference. Limitations, reasons for caution: This study was limited to samples with a motile sperm concentration of more over 1.0 × 10 6 in raw semen. Wider implications of the findings: These results demonstrated that sperm processing using the microfluidic device without centrifugation does not affect the fertilization or blastocyst development rate after ICSI and that the sperm processing procedure can be simplified by using this device. Trial registration number: not applicable